Influence of Product Features, Fear of Missing Out (FOMO), and Urgency Levels for Gen Z Purchasing Decisions - Azhari, Azlan (Fakultas Bisnis Institut Ilmu Sosial dan Bisnis Andi Sapada, 2025)
This study aims to examine the influence of product features , Fear of Missing Out (FOMO), and urgency level on Gen Z consumers purchasing decisions for smartphones during flash sale program on the Shopee platform. The research adopt a quantitative approach approach using a survey methods. The population in this study consists of Gen Z consumers who have purchased smartphones through Shopee's flash sale program, with a sample size of 100 respondents selected using accidental sampling. Data were collected via an on line questionnaire and analyzed using multiple linear regression via SPSS version 22, including validity, reliability, t-test, F-test, and coefficient of determination (R²). The results reveal that product features , FOMO, and urgency level each have a positive and significant effect on purchase decisions. Among these variables, product features have the strongest influence, followed by urgency and FOMO. The coefficient of determination (R²) value is 0.607, indicating that 60.7% of the variance in purchase decisions can be explained by the three independent variables. These​ findings highlights the importance of combining rational product attributes and emotional triggers in digital marketing strategies aimed at Gen Z consumers.